Outcome of Anastomotic Urethroplasty: Single-Center Experience - Faruque, Mohammad Salahuddin; Islam, AKM Anwarul; Alam, AKM Khurshidul; Rahman, Selina; Hossain, Faruk (Bangladesh Journal of Urology, 2020)
Objective: To determine the short term outcome of anastomotic urethroplasty. Material and Methods: From January 2013 to June 2015, 25 male patients underwent anastomotic urethroplasty at our center and were analyzed prospectively. Mean age was 28.1 years (range 13-50), average stricture length was 2.5 cm (range 1.5-2.5). Patients with post-prostatectomy stricture, stricture more than 2.5 cm in length or patients of stricture with neurogenic bladder and patients with any perineal disease were excluded from the study. Retrograde urethrogram and voiding cysto-urethrogram was done in every patient to assess stricture length and location. Stricture excision and end-to-end anastomosis of urethra with spatulation was performed in every patient. Minimum followup period was 6 months and maximum 30 months. All patients had obliterative stricture. Results: The mean operative time was 105 min (range 90-120). Four patients (16%) developed complications postoperatively. Wound infection occurred in 01 (04%) patient. Stricture recurrence found in 02 (08%) patients and erectile dysfunction in 01 (04%) patients. Twenty one patients (84%) had excellent outcome, Two (08%) needed optical internal urethrotomy and of them one (04%) failed to respond. Conclusion: Anastomotic urethroplasty has a high success rate of 92%. It is technically straightforward with minimal morbidity. Long term follow-up is strongly recommended for ultimate success. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.38-42